Development of a system-dynamics-based methodology for comprehensive community energy planning - Bugaje, Bilal (2022)
Global trends are leading to a rise in Energy Planning (EP) at the community-level, and Distributed Energy Resources at the residential-level, while seeking a more sustainable future; EP involves decision-making about energy systems. Whilst Community Energy Planning (CEP) aims to be holistic and participatory, it comprises multiple disjointed methods that lead to two challenges. The first challenge is hindrance to a holistic approach and understanding of the energy system, while the second challenge is hindrance to participation from diverse stakeholders. However, System Dynamics (SD), which is a methodology for mental and simulation models, looks promising as a basis for a comprehensive CEP methodology that would lead to a more holistic and participatory CEP.